Growth Characteristics and Production of Physalins from Physalis minima Hairy Roots in Shake Flasks - Gansau, Jualang Azlan; Mahmood, Marziah (Agriculture and Natural Resources, 2013)
This report described the growth characteristics and production of physalins from Physalis minima hairy roots in shake ﬂ ask culture. The presence of lateral branches in the inoculum had a negligible effect on the ﬁ nal root biomass dry weight (DW), speciﬁ c growth rate (μ), doubling time (td) and production of physalins. However, excising the primary and lateral root tips reduced μ and the total root length but not the ﬁ nal biomass. Mature root tissues were observed to accumulate more physalin B and F (1.55 and 3.74 mg.g-1 DW, respectively) compared to the root tips (0.65 and 1.47 mg.g-1 DW, respectively). Increasing the number of root tips from 2 to 12 and the medium volume signiﬁ cantly reduced μ and extended td. Decreasing the medium volume with a small number of inocula reduced td, improved the biomass and production of physalins and μ. Using a 100 mL ﬂ ask, four root tips cultured in 25 mL medium provided the optimum conditions for biomass (0.24 g DW) and production of physalins (1.68–3.5 mg.g-1 DW).